Jerusalem, Part 2. - Yardeni, Ada (De Gruyter, 2012)
The first volume of the Corpus Inscriptionum Iudaeae/Palaestinae covers the inscriptions of Jerusalem from the time of Alexander to the Arab conquest in all the languages used for inscriptions during those times: Hebrew, Aramaic, Greek, Latin, Syrian, and Armenian. The approximately 1,100 texts have been arranged in categories based on three epochs: up to the destruction of Jerusalem in the year 70, to the beginning of the 4th century, and to the end of Byzantine rule in the 7th century.